2010
DOI: 10.1540/jsmr.46.267
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope breath tests for assessing gastric emptying: A comprehensive review

Abstract: A stable isotope ([ 13 C]) breath test is a promising method for assessing gastric emptying, but it has not been pervasive yet in Japan. We think that there are some barriers to its popularization, including the uncertainty concerning its theoretical backgrounds, the ambiguity of analyzing and interpreting the data, and the lack of standard protocols for breath sampling. The aim of the present review is to break through these barriers. We hope this article could make the [ 13 C]-gastric breath test more maneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 36 publications
0
42
1
1
Order By: Relevance
“…The mean T-max 6–8 days after ESD was 75.4±13.6 min which was significantly longer compared with the mean T-max previously reported in healthy subjects (43.9±10.3 min) (16). This suggests that gastric emptying was delayed 6–8 days after ESD; however, gastric emptying beyond this operative period remains unknown.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…The mean T-max 6–8 days after ESD was 75.4±13.6 min which was significantly longer compared with the mean T-max previously reported in healthy subjects (43.9±10.3 min) (16). This suggests that gastric emptying was delayed 6–8 days after ESD; however, gastric emptying beyond this operative period remains unknown.…”
Section: Discussioncontrasting
confidence: 58%
“…The reference range of T-max was derived from 63 healthy volunteers by the Japan Society of Smooth Muscle Research; the mean ± SD of the T-max was 43.9±10.3 min (16). Gastric emptying following ESD in the patients with EGC in the present study is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With indirect methods, the emptying process is estimated by labeling the meal with a tracer. Tracer recovery via breath—or blood for acetaminophen—is used as a proxy to estimate GE . Breath testing (BT) is performed with a carbon isotope ( 13 C), which is absorbed and metabolized into CO 2 .…”
Section: Introductionmentioning
confidence: 99%